Optimizing Freight Terminal Location in Sarbagita Region: a Decision Analysis Approach using Analytic Hierarchy Process (AHP) - Ahmad Soimun; Nengah Widiangga; A.A. Bagus Oka Krisna Surya (School of Industrial and System Engineering, Telkom University, 2024)
Apart from serving regional freight transport, the availability of freight terminals is also urgently needed aspart of the urban transportation system. In providing a merchandise terminal, many considerations arerequired to create an effective and efficient transportation of merchandise in terms of connected cargo. Thepurpose of this research is to determine the location of the goods terminal so that logistics transportationservices in the Sarbagita area can run smoothly without being constrained by transportation problems. Thedata collection method was carried out by interviewing policy makers in the province of Bali and competenttransportation experts. Advanced analysis also uses Software Expert Choice which is a decision makingmethod, whose main tool is a hierarchy. After the data has been analyzed, conclusions are drawn using theAnalytic Hierarchy Process method. The results of the research on the criteria for the location of the freighttransport terminal include 6 variables including the suitability of RT/RW, traffic density, intermodalintegration, topographical conditions, accessibility and environmental impact. There are 4 suggestedalternatives, namely Mengwi, Soka Beach, Ubud, and Ida Bagus Mantra Gianyar. The choice of terminallocation obtained from the expert choice software on the 4 alternative location choices obtained that the bestlocation was the Mengwi area, Badung Regency (31.1%).